2004
DOI: 10.1039/b401754d
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic assembly of calcite microtrumpets: crystal tectonics in actionElectronic supplementary information (ESI) available: XRD pattern of trumpet-shaped structure. See http://www.rsc.org/suppdata/cc/b4/b401754d/

Abstract: Crystallisation of calcium carbonate in the presence of the polycarboxylate 1,3-diamino-2-hydroxypropane-N,N,N',N'-tetraacetate results in the formation of "microtrumpets" composed of nanocrystalline calcite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 9 publications
0
31
0
2
Order By: Relevance
“…We find that once we have only small amounts of the polycarboxylate present microtrumpets of calcite are produced [17] which are composed of what appear to be long nanocrystals of calcium carbonate (Fig. 7).…”
Section: Calcium Carbonate Formation With H 3 Heidi and H 5 Hpdtamentioning
confidence: 95%
“…We find that once we have only small amounts of the polycarboxylate present microtrumpets of calcite are produced [17] which are composed of what appear to be long nanocrystals of calcium carbonate (Fig. 7).…”
Section: Calcium Carbonate Formation With H 3 Heidi and H 5 Hpdtamentioning
confidence: 95%
“…It has been revealed that organic macromolecules play an important role in the assembly and growth of inorganic crystals in biological systems [3][4][5][6][7], which can control the phase, crystallinity, orientation and morphology of resulted mineral. The calcium carbonates with various morphologies, such as microtrumpets [8], hollow porous shell [9] and micropatterned single crystals [10], etc. have already been biomimetically prepared in laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…These include conformationally constrained peptides [95], polymers [96][97][98][99][100][101], self-assembled monolayers [102][103][104][105], other supramolecular assemblies [106] and small molecules [107][108][109][110][111] and have been reviewed elsewhere [85,[112][113][114]. These include conformationally constrained peptides [95], polymers [96][97][98][99][100][101], self-assembled monolayers [102][103][104][105], other supramolecular assemblies [106] and small molecules [107][108][109][110][111] and have been reviewed elsewhere [85,[112][113][114].…”
Section: Introduction To Biomineralizationmentioning
confidence: 99%